Early discharge in health facilities following vaginal delivery and its associated factors among mothers in four African countries: a cross-sectional study - Tadesse Tarik Tamir; Alebachew Ferede Zegeye; Berhan Tekeba; Melkamu Tilahun Dessie (BMJ Open)
Objective This study aimed to assess the prevalence of early discharge among women who gave vaginal delivery in health facilities.Design Cross-sectional study.Setting Four African countries.Participants A total weighted sample of 14 942 women who delivered vaginally in health facilities.Methods In this study, data were obtained from the recent Demographic and Health Survey data from four African countries. A total weighted sample of 14 942 women who delivered vaginally in a health facility was included. A multilevel mixed effect binary logistic regression model was fitted to identify significant factors associated with early discharge following health facility vaginal delivery. Statistical significance was determined using adjusted OR (odd ratio) with a 95% CI.Results The overall prevalence of early discharge following health facility vaginal delivery in four African countries was 30.91% (95% CI: 30.18% to 31.66%). Overall, first-born babies (AOR=0.7; 95% CI: 0.57 to 0.85), women with a high maternal body mass index (AOR=0.8; 95% CI: 0.71 to 0.89), women with multiple pregnancies (AOR=0.48; 95% CI: 0.31 to 0.74), women who reside in Burkina Faso (AOR=0.15; 95% CI: 0.12 to 0.18) and women who reside in Ghana (AOR=0.28; 95% CI: 0.24 to 0.33) had lower odds of early discharge following health facility vaginal delivery. On the other hand, women having no difficulty accessing health facilities (AOR=1.18; 95% CI: 1.05 to 1.33) and women delivering in private health facilities (AOR=1.46; 95% CI: 1.08 to 1.99) had higher odds of early discharge following health facility vaginal delivery.Conclusion Overall, in four African countries, a higher proportion of women who gave birth vaginally in health facilities were discharged home early without optimum immediate postpartum care. As a result, legislators, programmers and other stakeholders should make every effort to lessen the burden of early discharge, with a special focus on women who deliver in private health institutions.